2015
DOI: 10.1055/s-0035-1547295
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study on Less Invasive Surfactant Administration (LISA) in Preterm Infants<29 Weeks – Short and Long-term Outcomes

Abstract: Implementation of the LISA method on a neonatal ward was safe and feasible and was associated with less need for mechanical ventilation in infants >24 weeks. As our study was retrospective the observed trends for better pulmonary and neurocognitive outcomes should be interpreted with caution until results from randomized trials on the LISA procedure are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…The survival rate and disability-free rate in the intervention group tended to be higher than in the control group. Teig et al68) also published a 36-month follow-up of infants treated with MIST. This study showed that the intervention group performed better on the Bayley Scales Mental Developmental Index and Psychomotor Developmental Index than a historical control group.…”
Section: Problems To Be Solved In the Futurementioning
confidence: 99%
“…The survival rate and disability-free rate in the intervention group tended to be higher than in the control group. Teig et al68) also published a 36-month follow-up of infants treated with MIST. This study showed that the intervention group performed better on the Bayley Scales Mental Developmental Index and Psychomotor Developmental Index than a historical control group.…”
Section: Problems To Be Solved In the Futurementioning
confidence: 99%
“…In brief, the INSURE method and LISA, using either an NT or a LISAcath® catheter, are different ways of delivering SF that all provide effective therapies. Further, although a one‐off perturbation of cerebral oxygenation was observed in INSURE and LISA groups during SF administration, it was short, and no significant changes in the brain were detected in histological analysis …”
Section: Discussionmentioning
confidence: 99%
“…The meta‐analyses showed that there were no significant differences in the incidences of IVH, PVH, NEC, or ROP between the two groups, while thin catheter administration appeared to reduce the mortality rate, primarily in observational historical controlled trials. Two observational trials reported neurodevelopmental follow‐up outcomes, indicating no significant difference between the groups; however, both of them failed to achieved ≥80% follow‐up and had high risk due to incomplete outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the conventional method, thin catheter administration of surfactant reduced the need for invasive methods and MV, and also reduced the incidence of BPD. A series of trials with small sample sizes were conducted but, owing to the limited statistical power and the infants’ heterogeneous conditions, the results of these trials were inconsistent. Therefore, we performed a meta‐analysis of all controlled trials to systematically review the clinical outcomes of surfactant administration via a thin catheter in preterm infants.…”
Section: Introductionmentioning
confidence: 99%